Pre-season clinical assessment of the hip extensors, external rotators and abductors in competitive sprinters - Luiz Flores Fagnani, P.; Bittencourt, N. F. N.; Peralta, F. (British Journal of Sports Medicine, 2021)
Background Previous research has shown that muscle imbalances may be an important risk factor for lower limb injuries in runners. No studies have evaluated hip musculature imbalance in sprinters. Identifying pre-season strength and imbalances of the hip gluteal musculature can have an important impact on injury prevention within this population.